OPERATIONS PROGRAMMING BY MEANS OF THE RESTRICTIONS THEORY - Álvarez M, José (2004)
This article deals with Operations Programming diagnosis within small and micro-enterprises (Pymes) in Peru, Lima's Parque Industrial Villa El Salvador's wooden furniture sector. A proposal of a continuous improvement of operations programming is set upon, out of the information compiled and the Restrictions Theory application.